2001
DOI: 10.1890/0012-9658(2001)082[0018:dpabnt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENTAL PLASTICITY ALLOWSBETULA NANATO DOMINATE TUNDRA SUBJECTED TO AN ALTERED ENVIRONMENT

Abstract: We investigated how three co‐dominant arctic shrubs (Betula nana, Salix pulchra, and Ledum palustre ssp. decumbens) responded to long‐term treatment with N+P fertilizers and greenhouses in a factorial field experiment at Toolik Lake, Alaska. Our goal was to understand the relationship between growth of individuals and species abundance in the community, and the mechanism by which one species achieves dominance under changed environmental conditions. We compared aboveground growth and allocation patterns in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…The soil heat flux, on the other hand, depended strongly on soil thermal properties. This is in contrast to the studies by Blok et al (2010) and Briggs et al (2014), which identified soil shading as important control of local permafrost thaw. A schematic of the differences we found between key components of the dwarf shrub and wet sedge system can be found in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The soil heat flux, on the other hand, depended strongly on soil thermal properties. This is in contrast to the studies by Blok et al (2010) and Briggs et al (2014), which identified soil shading as important control of local permafrost thaw. A schematic of the differences we found between key components of the dwarf shrub and wet sedge system can be found in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…It could also have to do with the fact that B. nana is able to allocate large proportions of its biomass belowground and can translocate substantial amounts of nutrients between plant parts during the season (Chapin, Johnson, & McKendrick, 1980). This high plasticity helps it to respond quickly to altered environmental conditions (Bret-Harte et al, 2001). Therefore, when B. nana is suppressed by grazers, it is possible that comparatively more C is allocated to the roots, which may stimulate fungal growth.…”
Section: Relativeabundance(%)mentioning
confidence: 99%
“…In previous studies, Betula nana L., and other birch species (Betula populifolia Marsh., Betula papyrifera Marsh., Betula alleghaniensis Britt.) have been found to show a higher degree of plasticity than other species found at higher altitudes [44,45]. While larch with an upright tree form grew faster than birch, larch with a 'cushion' or more stunted form grew more slowly than birch [46].…”
Section: Species-specific Height-diameter Relationshipmentioning
confidence: 99%